NUEVA ESPECIE DE GLOTTIDIA (BRACHIOPODA, LINGULIDAE) DEL MIOCENO (FORMACIÓN CAMACHO) DE URUGUAY (Ameghiniana, 2014)
A new species of Lingulidae, Glottidia bravardi n. sp. is described from the Camacho Formation (Miocene) of Uruguay. This species was mentioned in the bibliography as "Lingula bravardi" (nomen nudum), According to the ecologic requirements of the extant species of the genus, the species described here must have lived in a sea with tropical to subtropical characteristics.